Forecast for thermal water use from Upper Jurassic carbonates in the Munich region (South German Molasse Basin). (March 2016) - Dussel, M.; Lüschen, E.; Thomas, R.; Agemar, T.; Fritzer, T.; Sieblitz, S.; Huber, B.; Birner, J.; Schulz, R.
Highlights: A 3D structure model was created for the Munich area in the S. German Molasse Basin. Multidisciplinary characterization of the Upper Jurassic reservoir was performed. A 3D FE numerical model was calibrated by thermal and hydraulic measurements. Long-term forecasts show minor hydraulic interferences between adjacent wells. Abstract: A numerical thermo-hydraulic 3D model of the geothermal Upper Jurassic Aquifer (Malm) in the Munich region was developed based on a multidisciplinary reservoir characterization. The mutual hydraulic and thermal interference of 13 deep geothermal plants with 28 wells, pressure and temperature changes of the aquifer, and the total geothermal potential of the reservoir were investigated. Long-term (50 years) simulations forecast temperature decreases which only occur in the close vicinity of the individual reinjection wells, and mostly minor hydraulic interference in adjacent wells. Operators can use the 3D finite-element model, for the sustainable management of the thermal reservoir after updating the input by additional well data.